2008
DOI: 10.1111/j.1467-8683.2008.00662.x
|View full text |Cite
|
Sign up to set email alerts
|

Audit Committee and Firm Value: Evidence on Outside Top Executives as Expert‐Independent Directors

Abstract: Manuscript Type: EmpiricalResearch Question/Issue: We examine the relation between independence of audit committee and firm value with a sample of Fortune 200 companies. Research Findings/Insights: Using a sample of Fortune 200 companies and defining top executives of other publicly traded firms as expert-independent directors and controlling for firm specifics, board features, and individual director characteristics, we find the presence of expert-independent directors on board and in the audit committee enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
168
3
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(198 citation statements)
references
References 25 publications
24
168
3
3
Order By: Relevance
“…In UK, as in other countries, audit committees are responsible for monitoring the integrity of the financial statements of the company and for the oversight of the company's systems of internal control and risk management (FRC 2010). Consistent with the expectations, research finds that appropriately staffed audit committees (in terms of having independent non-executives and especially financial experts sitting on them) perform a better oversight function and help enhance firm value (Chan and Li 2008). Recently, Khan et al (2013) find the presence of an audit committee to have a positive impact on CSR disclosures.…”
Section: Women On Board There Is a Growing Societal As Well As Regulsupporting
confidence: 56%
“…In UK, as in other countries, audit committees are responsible for monitoring the integrity of the financial statements of the company and for the oversight of the company's systems of internal control and risk management (FRC 2010). Consistent with the expectations, research finds that appropriately staffed audit committees (in terms of having independent non-executives and especially financial experts sitting on them) perform a better oversight function and help enhance firm value (Chan and Li 2008). Recently, Khan et al (2013) find the presence of an audit committee to have a positive impact on CSR disclosures.…”
Section: Women On Board There Is a Growing Societal As Well As Regulsupporting
confidence: 56%
“…Various studies have been conducted in different sectors and geographic location across the globe such as Choi et al (2006), Chan and li (2008), Nazir et al (2009), Dunstan et al (2011), Rouf (2011), Vintila and Gherghina A. Khan et al / Accounting 3 (2017 123 (2013) found that there was a positive and significant relationships between board independent director and firm value. The presence of non-executive directors on board gives a positive signal to the investors and shareholders in particular and stakeholders in general that affairs of the firms are prudently monitored which also increase public confidence and subsequently add to firm value (Hassan & Butt, 2009).…”
Section: Board Independencementioning
confidence: 99%
“…Audit committee independence has been associated with firm value (Chan and Li, 2008) and lower debt financing costs (Anderson, Mansi, and Reeb, 2004). We therefore control for the proportion of independent non-executive directors on the audit committee.…”
Section: Control Variablesmentioning
confidence: 99%